Hall of Horrors Claws! - Stine, R. L. (Scholastic Paperbacks, 2011)
Mickey is put in charge of his vacationing neighbors' cat Bella. His best friend, Amanda, comes along to help out. All they have to do is make sure Bella has enough to eat and doesn't destroy the furniture. Seems simple enough. But Bella escapes from the house and is hit by a truck. Mickey feels awful. What is he going to do? Amanda has an idea to replace the cat with a look-alike from the pet store. They find a cat that looks exactly like Bella ... but this cat is more than it seems